ANALISIS SPASIAL TITIK DAN JALUR EVAKUASI DALAM MITIGASI PENGURANGAN RISIKO BENCANA BANJIR DI KECAMATAN MANDONGA KOTA KENDARI - Hasddin Hasddin; Erny Tamburaka (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
This study analyzes the distribution of flood areas and the determination of evacuation sites and routes in Mandonga District, Kendari City. This research uses a quantitative design and a survey. Data were analyzed spatially with ArcView 3.2 application. The results showed that the floods that occurred in Mandonga District, Kendari City during 2015-2018 were 416.23 ha or around 37.45% of the total area of ​​Mandonga District (1,111.47 ha), spread throughout the region (in six villages). There are six (6) points that are suitable as main evacuation points for flood refugees in Mandonga District, 1 point in Labibia Village, 2 points in Wawombalata Village, and 3 points in Mandonga Village. There are 11 path points namely; Jl. Imam Bonjol; Jl. Subsidy; Jl. Sawerigading (Anggilowu); Jl. Sawerigading (Mandonga); Jl. Taridala; Jl. Lasandara; Jl. Made Sabara; Jl. Tax; Jl. Welado; Jl. Supu Yusuf; and Jl. Sidendreng.